2004
DOI: 10.1111/j.1460-9568.2004.03438.x
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical involvement in verbal encoding strategies

Abstract: The lateral prefrontal cortex is critical for the control and organization of information in working memory. In certain situations, effective reorganization can attenuate task difficulty, suggesting a dissociation between lateral prefrontal activity and basic memory demand. In a verbal working memory task, we investigated the enhancement of performance that occurs when incoming information can be reorganized into higher-level groups or chunks. In the fMRI scanner, volunteers heard and repeated a sequence of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
104
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 46 publications
14
104
0
2
Order By: Relevance
“…However, the RT on reorder trials did not differ as a function of subsequent memory performance, nor did it correlate with DLPFC subsequent memory effects. These findings are consistent with studies that have reported increased DLPFC activation in contrasts between conditions that were matched for difficulty (Cabeza et al, 2002) or during performance of the less difficult of two tasks (Braver and Bongiolatti, 2002;Bor et al, 2004). Additionally, in the extant encoding literature, four of the five encoding studies that reported significant accuracy differences between encoding tasks do not report DLPFC subsequent memory effects in either the more difficult or the relatively easier condition (Chee et al, 2003;Clark and Wagner, 2003;Reynolds et al, 2004;de Zubicaray et al, 2005) (but see Baker et al, 2001).…”
Section: Dlpfc Activity and Ltm Formationsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the RT on reorder trials did not differ as a function of subsequent memory performance, nor did it correlate with DLPFC subsequent memory effects. These findings are consistent with studies that have reported increased DLPFC activation in contrasts between conditions that were matched for difficulty (Cabeza et al, 2002) or during performance of the less difficult of two tasks (Braver and Bongiolatti, 2002;Bor et al, 2004). Additionally, in the extant encoding literature, four of the five encoding studies that reported significant accuracy differences between encoding tasks do not report DLPFC subsequent memory effects in either the more difficult or the relatively easier condition (Chee et al, 2003;Clark and Wagner, 2003;Reynolds et al, 2004;de Zubicaray et al, 2005) (but see Baker et al, 2001).…”
Section: Dlpfc Activity and Ltm Formationsupporting
confidence: 78%
“…DLPFC activation has also been reported in studies investigating "chunking," which involves processing of relationships to build higher-level groupings among items that are active in WM (Bor et al, 2004). Reasoning tasks, which entail extraction and integration of relationships among verbal propositions (Bunge et al, 2005), mathematical operations , or complex visual objects (Christoff et al, 2001;Kroger et al, 2002) active in WM have also been shown to activate the DLPFC.…”
Section: Dlpfc and Wm Processingmentioning
confidence: 95%
“…Referencing to LTM may have induced the VLPFC activity, which was observed during both recoding and manipulation processes. VLPFC activity was reported during a knowledge-based chunking task, which required subjects to retrieve task-relevant information from LTM (Bor et al, 2004). Similar VLPFC activity was observed during stimulus-response linkage tasks (Petrides, 2002;Prince et al, 2005;Hanakawa et al, 2006).…”
Section: The Vlpfc and The Role Of Ltm In Wm Manipulationmentioning
confidence: 62%
“…In addition, the tasks used varied not only in their associative demands, but also required different processing strategies. Whereas item memory seems to depend on MTL structures (Eichenbaum et al, 2007;Squire, Stark, & Clark, 2004), story processing requires the strategic manipulation and organization of information, which largely depends on the prefrontal cortex (Addis & McAndrews, 2006;Bor, Cumming, Scott, & Owen, 2004;Fletcher, Shallice, & Dolan, 2000). Therefore, the results may reflect differences in task strategy as opposed to differences in associative task demands.…”
Section: Discussionmentioning
confidence: 82%